A secular need : Islamic law and state governance in contemporary India - Redding, Jeff (Global South Asia., 2020)
"Islamic law's relationship to secular governance is a fraught one in contemporary discussions. Whether from the perspective of Islamic law's advocates, secularism's partisans, or publics caught in the crossfire, many people see the relationship between Islam and secularism as antagonistic. Moreover, the relationship between Islamic law and secularism seems increasingly discordant, with recent developments in the United States (e.g., calls for "shari'a bans" in U.S. courts), Western Europe (such as legal limitations on headscarves and mosques), and the Arab Middle East (such as conflicts between secularist old-guards and Islamist revolutionaries) indicating that unsteady coexistences are transforming into outright hostilities. This book's exploration of an Indian non-state system of Muslim dispute resolution-formally known as the dar ul qaza system, but commonly referred to as a system of "Muslim courts" or "shariat courts"-challenges conventional narratives about the inevitable opposition between Islamic law and secular forms of governance, and the impossibility of their coexistence. Moreover, it demonstrates how secular law and governance in India does not and cannot work without the significant assistance of non-state Islamic legal actors. For example, the conciliation-oriented Indian family court system is insufficient for handling divorce petitions brought by Muslim women seeking to unilaterally disassociate from their Muslim husbands. This volume shows how in these situations and others, Indian state secularism needs the Islamic non-state-so much so that this intense need often erupts into a complicated set of love-hate politics towards India's Muslims"--